2010
DOI: 10.1007/s00592-010-0220-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy and tolerability of miglitol in Chinese patients with type 2 diabetes mellitus inadequately controlled by diet and sulfonylureas

Abstract: The objective of this study is to examine the efficacy and tolerability of miglitol with respect to improving glycemic control in Chinese patients with type 2 diabetes mellitus inadequately controlled by diet and sulfonylurea treatment. This was a randomized, double-blinded, placebo-controlled, multicenter study. A total of 105 patients were randomized to receive 24 weeks of treatment with miglitol (n = 52; titrated from 50 mg to 100 mg 3 times daily) or placebo (n = 53). Concomitant sulfonylurea treatment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Miglitol is an aGI, which improves postprandial hyperglycemia [4,5]. In general, aGIs should be taken just before meals [6].…”
Section: Introductionmentioning
confidence: 99%
“…Miglitol is an aGI, which improves postprandial hyperglycemia [4,5]. In general, aGIs should be taken just before meals [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro and in vivo studies have shown that oleuropein and its derivate hydroxytyrosol possess a wide range of biochemical and pharmacological properties 7 . It was also reported that ble state in diabetes 9 . In fact, the inhibitory activity of oleuropein s aglycon and luteolin glucosides luteolin-7-O-β-glucoside and luteolin-4 -O-β-glucoside against pancreatic amylase were determined 8 .…”
mentioning
confidence: 84%
“…Although their safety and tolerability has been widely evaluated due to the common clinical use of these drugs, their lack of specificity has been seen to produce several gastrointestinal side effects like abdominal cramping, flatulence and diarrhea (171)(172)(173)(174). Natural alpha-glucosidase and alpha-amylase inhibitors are being investigated as new candidates to control hyperglycemia in diabetic patients, but few data are available regarding the negative effects they might produce.…”
Section: Side Effects Of Natural Alpha-amylase Inhibitorsmentioning
confidence: 99%